Efektivitas Ulangan Harian Menggunakan Wondershare Quiz Creator Terhadap Hasil Belajar IPS Materi Dinamika Interaksi Manusia pada Peserta Didik Kelas 7 UPT SMP Negeri 4 Mojokerto - Yuddy Christiawan (STAI Nurul Islam Mojokerto, 2021)
The aims of this research is determine the effectiveness of daily tests using Wondershare quiz creator of the acquisition of knowledge of students compared to the daily test manually in the second half of 7th grade students in UPT SMP Negeri 4 Mojokerto. This research is a quantitative research with experimental design guidance (guide experiment design) with pretest posttest design pattern. 7G class as the control class and the class as a class experiment 7H treated with replications using Wondershare quiz creator. Data were obtained as follows: The results of the validation aplikasi Wondershare quiz creator of validator with an average value of 4.94 with a value of excellent category, validating the instrument about an average value of 5 with excellent category. Validation instrument student questionnaire responses on average 4 value with very good category. Test the hypothesis with a significance level (sig.2-tailed) was 0,000 less than 0.05 then Ho is rejected and H1 accepted with no criteria for effective use of learning outcomes assessment tool using Wondershare Quiz Creator of the value before (pretest) and after (posttest). Constraints in the use Wondershare especially when the power to the computer is off will cause students to stop the test, but can be overcome by installing a power storage device power supply. Based on the findings, it was concluded that there is a daily test the effectiveness of the use of Wondershare Quiz Creator is an honest students build character, confidence, because students get random questions that appear on the computer with other students. so the opportunity to cheat or ask other students is very difficult to do. More students master the knowledge because of problems in the design more interesting by giving the animation in the form of pictures and video in daily tests. Better use of assessment of student learning outcomes-based computer by using aplikasi Wondershare Quiz Creator is more effective teachers because it can facilitate teachers in the process of correction results of a test, questions and answers have been documented in the aplikasi so that once students click submit complete replay, it will automatically answer results and student scores shown on a computer screen.